IMPLEMENTASI PELAYANAN SURAT IZIN MENGEMUDI (SIM) ONLINE DI SATUAN PENYELENGGARA ADMINISTRASI SIM KOTA PROBOLINGGO - Risqina, Venanda Octa; Septiandika, Verto; Puspitarini, Renny Candradewi (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2024)
The implementation of technology in public services continues to evolve, including in the issuance of Driving Licenses (SIM). The Probolinggo City Satpas (Driver's License Issuance Unit) has introduced an online SIM service innovation to enhance convenience and efficiency for the community. This research aims to examine the implementation of online SIM services at the Probolinggo City Satpas. This qualitative study uses a descriptive method to analyze data obtained through interviews and observations at the Probolinggo City Satpas. Charles O. Jones' implementation model, which includes three variables (organization, interpretation, and application), is the focus of this research. The online SIM service at the Probolinggo City Satpas has been running well according to procedures and operational standards. Positive indicators include service procedures, completion time (15-30 minutes), costs in accordance with regulations, product and staff competence, as well as the friendliness of the Satpas team. Outreach is also conducted in schools and factories. Online SIM data is directly connected to the National Police Traffic Corps (Korlantas Polri). The implementation of online SIM services at the Probolinggo City Satpas is considered successful and beneficial for the community.